Line list for the ground state of CaF. (May 2018) - Hou, Shilin; Bernath, Peter F.
Highlights: Analytical Extended Morse Oscillator (EMO) potential function derived for CaF. Ground state dipole moment function calculated ab initio. Line lists calculated for 40 CaF, 42 CaF, 43 CaF, 44 CaF, 46 CaF and 48 CaF vibration-rotation transitions. Useful for spectra of high temperature environments such as hot super-Earth exoplanets. Abstract: The molecular potential energy function and electronic dipole moment function for the ground state of CaF were studied with MRCI, ACPF, and RCCSD(T) ab initio calculations. The RCCSD(T) potential function reproduces the experimental vibrational intervals to within ∼2 cm −1 . The RCCSD(T) dipole moment at the equilibrium internuclear separation agrees well with the experimental value. Over a wide range of internuclear separations, far beyond the range associated with the observed spectra, the ab initio dipole moment functions are similar and highly linear. An extended Morse oscillator (EMO) potential function was also obtained by fitting the observed lines of the laboratory vibration-rotation and pure rotation spectra of the 40 CaF X 2 Σ + ground state. The fitted potential reproduces the observed transitions ( v  ≤ 8, N  ≤ 121, Δ v  = 0, 1) within their experimental uncertainties. With this EMO potential and the RCCSD(T) dipole moment function, line lists for 40 CaF, 42 CaF, 43 CaF, 44 CaF, 46 CaF, and 48 CaF were computed for v  ≤ 10, N  ≤ 121, Δ v  = 0–10. The calculated emission spectra are in good agreement with an observed laboratory spectrum of CaF at a sample temperature of 1873 K.